Effects of Dietary Supplementation of Scutellaria baicalensis Extract During Early Lactation on Milk Production of Dairy Cattle - K. Olagaray; Michael Brouk; F. Robert; E. Dupuis; B. Bradford (Kansas Agricultural Experiment Station Research Reports, 2017)
Multiparous Holstein cows (n = 122) were used in a randomized block design to determine the effect of short-term and long-term postpartum administration ofScutellaria baicalensisextract (SBE) on 305-day milk yield, 120-day milk component yield, and early lactation milk markers of inflammation and metabolic function. Treatments were (1) control, (2) short-term (5-day) administration of the SBE (SBE5), and (3) longterm (60-day) administration of the SBE (SBE60). Treatments were included in a treatment pellet that was identical to the control pellet in ingredient source and composition except for the extract, and both pellets were provided via an automated milking system. Milk samples were collected on day 1, 3, and once during days 5–12 of lactation, followed by weekly sampling for the remainder of the 120 days collection period. Milk samples collected in the first 2 weeks were used for biomarker analysis (haptoglobin and β-hyroxybutyrate [BHBA]), and all samples were used for composition analysis. Cows were scored for body condition every 2 weeks prepartum and postpartum. Milk production, programmed pellet allocation, and actual provision of both pelleted feeds were recorded daily. There was no difference in daily treatment pellet feeding between SBE5 and SBE60 for the first 5 days of lactation. Total pellet intake was greater for SBE60 than SBE5 and control cows during the treatment period (weeks 1–9), but not during the carryover period (weeks 10–36). No treatment effects were observed for body condition, milk haptoglobin, or milk BHBA. Whole-lactation milk yield was increased for SBE60 compared to control, but SBE5 did not differ from control. Milk lactose and fat yields were significantly greater and milk protein yield tended to be greater for SBE60 than control. Treatment SBE60 decreased somatic cell count (SCC) compared to control during weeks 3–5 and 8, whereas SBE5 did not affect SCC. Mastitis incidence was lesser for both SBE5 and SBE60 compared to control. Time to pregnancy did not differ, but retention in the herd tended to be greater for SBE60 than control. In conclusion, despite no detected treatment effects on BCS or milk biomarkers of inflammation and metabolic status, supplementation of postpartum dairy cows withScutellaria baicalensisextract for 60 days was effective at decreasing mastitis incidence and increasing milk yield.
Keywords: polyphenol; dairy cow; transition; inflammation